National Survey of School Employees: COVID‐19, School Reopening, and Student Wellness. (2nd March 2021) - Pattison, Krista L.; Hoke, Alicia M.; Schaefer, Eric W.; Alter, Jeanie; Sekhar, Deepa L.
ABSTRACT: BACKGROUND: During spring 2020, COVID‐19 forced widespread United States school building closures in an unprecedented disruption for K‐12 students and staff. Partnering with the American School Health Association (ASHA), we sought to identify areas of concern among school staff planning for school reopening with the goal of addressing gaps in resources and education. METHODS: This 16‐item web‐based survey was distributed via email to 7467 ASHA members from May to June 2020. Topics focused on 3 Whole School, Whole Community, Whole Child components: physical environment, health services, and mental health. Chi‐square tests were used to identify differences in responses by school characteristics and school role on each survey item. RESULTS: A total of 375 respondents representing 45 states completed the survey. The majority were female (91.7%), white (83.4%) and non‐Hispanic (92.2%), and school nurses (58.7%). Priority concerns were feasibility of social distancing (93.6%), resurgence of COVID‐19 (92.8%), and the availability of health supplies (88.8%). CONCLUSION: Understanding staff concerns in the context of the Whole School, Whole Community, Whole Child model better positions the school community to address ongoing gaps and changing needs as schools continue to address COVID‐19 complications.